Design of a low-profile dual-band 8-element array antenna - Yeo, Chee Leng. (2013)
This report provides an account of the process of designing a low profile dual band antenna using High Frequency Structural Simulator. The antenna consists of components such as a feed line, dipoles and a substrate of dielectric constant of 4.4 (FR4). The function includes resonating and receiving frequency at 925MHz and 1.8GHz. The antenna can be used for frequency tracking. This report will present the steps taken during FYP from the researching phase to achieving the final results of the design. Results acquired from the simulation will be presented and discussed. The final results obtained fulfil the required frequency along with a radiation pattern which can be further improved.